Teaching and learning second language pragmatics for intercultural understanding - McConachy, Troy, 1980-; Liddicoat, Anthony J. (Routledge, 2022)
"This collection argues for the need to promote intercultural understanding as a clear goal for teaching and learning pragmatics in second and foreign language education. The volume sees the learning of pragmatics as a challenging yet enriching process whereby the individual expands their capacity for understanding how meaning making processes influence social relationships and how assumptions about social relationships shape the interpretation and use of language in context. This locates pragmatics within a humanistically oriented conception of learning where success is defined relative to the enrichment of human understanding and appreciation of difference. The book argues that intercultural understanding is not an "add on" to language learning but central to the learner's ability to understand and construct meaning with individuals from diverse linguistic and cultural backgrounds. Chapters analyse teachers' and learners' ways of making sense of pragmatics, how their assumptions about social relationships impact their perceptions of language use, and how reflection on pragmatic judgments opens up possibilities for developing intercultural understanding. This book will be of interest to students and scholars in intercultural communication, language education, and applied linguistics"--